Lending Cycles and Real Outcomes: Costs of Political Misalignment - Çağatay Bircan; Saka Orkun (London School of Economics and Political Science (LSE), European Institute, 2018)
We document a strong political cycle in bank credit and industry outcomes in Turkey. In line with theories of tactical redistribution, state-owned banks systematically adjust their lending around local elections compared with private banks in the same province based on electoral competition and political alignment of incumbent mayors. This effect only exists in corporate lending as opposed to consumer loans. It creates credit constraints for firms in opposition areas, which suffer drops in employment and sales but not firm entry. There is substantial misallocation of financial resources as provinces and industries with high initial efficiency suffer the greatest constraints.
Keywords: 330; Bank credit; Electoral cycle; State-owned banks; Credit misallocation